Accuracy of Heart Auscultation Examination by General Practitioners From Various Levels of Competency in Detection of Heart Abnormality in Basic School Children - Annisa Permatasari; Deny Salverra Yosy; Achirul Bakri; Ria Nova (HM Publisher, 2022)
Background. Most of heart defects in children do not show typical clinical symptoms. Ten percent of the cases are late detected. Echocardiography is an examination with high sensitivity and specificity in detecting heart defects in children, but it cannot be performed by all health workers, expensive and not always available in hospitals. Auscultation is an important part of a physical examination that inexpensive, easy examination, and becomes a competency of all doctors. The aim of this study to determine the accuracy of the screening method by listening to murmurs on heart auscultation by various levels of physician competence. Methods. This is a diagnostic test of 250 elementary school children held in the pediatric ward of dr. Mohammad Hoesin Palembang from September to November 2019. The auscultation examination was performed by three pediatrics resident from three stages (i.e. junior, middle and senior), followed by echocardiography examinations by a pediatric cardiologist. Results. The highest sensitivity of auscultation was found in senior resident, 42.4%, while the lowest was found in junior resident, 12.1%. The results of the kappa analysis of the cardiac auscultation examination on the three examiners showed a poor level of agreement on junior stage compared to senior resident (k = 0.189; CI = 0.033-0.346) and the level of agreement was sufficient in junior stage compared to middle stage resident (k = 0.297; CI = 0.134 -0.461) and middle stage compared to senior resident (k = 0.301; CI = 0.147-0.456). Conclusion. Experience and length of learning will affect the accuracy of the auscultation examination in detecting heart defects in children.